ANALISIS PENGEMBANGAN APLIKASI PSYCHOMOTOR VIGILANCE TASK (PVT) SEBAGAI ALAT UJI KESIAPAN BERTUGAS PENGEMUDI KENDARAAN TEMPUR - Uman Sukmada; Sigit Permana; Hardianto Iridiastadi; R. DJoko Andreas Navalino (DAS Institute, 2022)
Fatigue has been stated as one of the main factors causing accidents in various countries. One of the efforts that can be made to prevent the risk of an accident is to detect as early as possible the driver's condition before starting the trip. One example of a driving profession is the driver of a combat vehicle. Busy work schedules and changing service schedules can result in combat vehicle drivers experiencing a decrease in the quality and quantity of sleep associated with increased fatigue at work. Therefore, this study aims to evaluate the level of fitness for the duty of soldiers. The research was held at the TNI Soldier Education Center using a type of Tank fighting vehicle. This study used the Psychomotor Vigilance Task (PVT) application as a measuring tool for data collection, with a total of 8 respondents. Data processing using Wilcoxon's non-parametric statistical test. The results showed that there was no significant difference in the average value of response time and drowsiness, but the number of misses showed a significant difference in conditions after driving for 2 hours, and after driving for a total of 3 hours.